ORIGINAL PAPER Combined interferon-alpha-2b and ribavirin therapy in patients with recurring chronic hepatitis C (genotype 1) following liver transplantation in Hungary - Lengyel, Gabriella; Kóbori, László; Fehérvári, Imre; Nemes, Balázs; Görög, Dénes; Patonai, Attila; Sárváry, Enikö; Varga, Marina; Hagymási, Krisztina; Perner, Ferenc; Fehér, János; Tulassay, Zsolt (Archives of Medical Science, 2005)
Objectives: Hepatitis C virus (HCV) recurrence after liver transplantation is universal and leads to chronic hepatitis and cirrhosis. Combined interferon and ribavirin therapy represents the accepted treatment for recurrent chronic hepatitis C following liver transplantation, according to the literature. Our aim was to assess the efficacy and safety of the recommended combined interferon and ribavirin therapy, and evaluation of the rate of long-term remission under Hungarian circumstances. Methods: 16 patients with chronic recurrent hepatitis C, who had been HCV-PCR positive (genotype 1b), received combined treatment with interferon-alpha-2b (3 MU three times a week) and ribavirin (800-1000 mg daily) for 12 months following transplantation. 12 patients have completed the therapy. Liver biopsies were performed before commencing and after concluding treatment in every patient. Virological responses at completion of the 12-month-long treatment and at the end of the subsequent 6-month-long follow-up period served as endpoints for the evaluation. Results: At completion of the 12-month-long treatment 3 patients became HCV-PCR-negative. All three patients remained negative at six months following completion of the treatment. Conclusions: Efficacy and safety of the combined treatment of transplanted patients were similar to the therapeutic results in patients with chronic hepatitis C without liver transplantation.